The Design of Heart Rate Detector and Body Temperature Measurement Device Using ATMega16 - Hudha Wijaya, Nur; Ahmad Fauzi, Fajar; T.Helmy, Elsayed; Thanh Nguyen, Phong; Andri Atmoko, Rachmad (Journal of Robotics and Control (JRC), 2020)
This research will discuss health services in the role of diagnostics and life support. The system designed is a system that is able to provide information on the user's health condition, in this case, is a measure of heart rate and body temperature. In taking heart rate data using a heart rate sensor (fingertip sensor). This system works taking data from the blood flow on the index finger for the 60s, the data will be displayed through the LCD. For body temperature parameters the data collection uses the LM35 temperature sensor. Changes in sensor heat will be converted into electricity, which is translated into digital form through a 10-bit ADC that is processed by the ATMega 16 microcontroller and displayed to the LCD. The results of an ideal measurement show the error of each parameter heart rate and body temperature min 1.702% and 0.55%